2009
DOI: 10.1038/ajh.2009.17
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Sympathetic Premotor Neurons Contributes to Sympathetic Activation in Renovascular Hypertension

Abstract: The data suggest that the hypertension and sympathoexcitation in 2K-1C rats were associated with an increase in oxidative stress within the RVLM, the PVN and systemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 34 publications
8
125
0
4
Order By: Relevance
“…In the previous study, we observed an imbalance of the autonomic control of the cardiovascular system (sympathetic overactivity and impaired parasympathetic activity) in the 2K1C model of renovascular hypertension . Moreover, augmented ROS production mediates the Ang II actions and results in a sympathetic tone imbalance (Zimmerman et al, 2004;Gao et al, 2005;Oliveira-Sales et al, 2009), which worsens cardiovascular disease processes (Abboud, 2010;Campos et al, 2011). Additionally, in models of infused or endogenous (2K1C) Ang II, inhibition of ROS partly attenuates hypertension, indicating that Ang II-induced ROS is important for vasoconstriction in these models (Taniyama and Griendling, 2003).…”
Section: K1c Hypertension Affects Bone Marrow Cellsmentioning
confidence: 99%
“…In the previous study, we observed an imbalance of the autonomic control of the cardiovascular system (sympathetic overactivity and impaired parasympathetic activity) in the 2K1C model of renovascular hypertension . Moreover, augmented ROS production mediates the Ang II actions and results in a sympathetic tone imbalance (Zimmerman et al, 2004;Gao et al, 2005;Oliveira-Sales et al, 2009), which worsens cardiovascular disease processes (Abboud, 2010;Campos et al, 2011). Additionally, in models of infused or endogenous (2K1C) Ang II, inhibition of ROS partly attenuates hypertension, indicating that Ang II-induced ROS is important for vasoconstriction in these models (Taniyama and Griendling, 2003).…”
Section: K1c Hypertension Affects Bone Marrow Cellsmentioning
confidence: 99%
“…64 The paraventricular nucleus of the hypothalamus is most likely also involved in the ROS-mediated neural mechanism of hypertension. 60,66 There is evidence that other regions of the brain are likewise involved in ROSmediated hypertension. These investigations suggest that increased intracellular superoxide production in the subfornical organ is critical to the development of AT-II-induced hypertension.…”
Section: Urotensin-iimentioning
confidence: 99%
“…Regarding reactive oxygen species in the RVLM, our laboratory and others have shown that Ang II-derived superoxide anions accumulation in the RVLM is critical for the pathogenesis of neurogenic hypertension (Figure 1) [12,17,18,[30][31][32]. The increase of superoxide anions leads to changes in ion channels, particularly calcium and potassium channels, altering neuronal properties in RVLM resulting in increase in sympathetic nerve activity and increase in blood pressure [33].…”
Section: Reactive Oxygen Species In the Rostral Ventrolateral Medullamentioning
confidence: 99%
“…Moreover, adenoviral vectors encoding small interfering RNA to selectively silence Nox2 or Nox4 (two isoforms of the NADPH oxidase) expression in the subfornical organ demonstrate that both Nox2 and Nox4 are required for the full vasopressor effects of brain Ang II [17,18]. One possible downstream mechanism of the activation of AT1R in the SFO and subsequent production of ROS is the superoxide-mediated intracellular calcium influx observed in neuroblastoma Neuro-2A cells, which is inhibited by the adenoviral-mediated expression of a dominant-negative isoform of Rac1 (AdN17Rac1), a critical component for NADPH oxidase activation and superoxide production.…”
Section: Introductionmentioning
confidence: 99%